Three-Dimensional Stability Problems of Composite Materials and Composite Construction Components - Guz, A.N.; Babić, I.U. (Engineering Transactions, 1979)
Three-dimensional static and dynamic linearized problems of stability were posed both for compressible and incompressible bodies. In the case of homogeneous sub-critical deformations the general solutions to these problems were constructed. Corresponding variational principles formulated and their validity was proved. In the framework of were the three-dimensional linearized theory, plane and spatial problems of instability of deformation of layered and fibre materials both at small and at large elastic deformations were studied. The elastic stability of bars, plates and rolled shells made of composite classical materials was studied and the regions of applicability of and improved theories applied here were determined.